Phytochemical Screening, Evaluation of Antioxidant Activity, Total Phenolic and Flavonoid Content of Selected Nepalese Medicinal Plants (Butwal Campus Journal, 2022)
This research work aimed to analyze the phytochemicals, total phenolic, flavonoid contents, and antioxidant properties of four selected medicinal plants of Gulmi and Rupandehi districts using in vitro studies. They were Dioscorea bulbifera from Gulmi, the other three Aegle marmelos, Nyctanthes arbortristis, Urtica dioica from Rupandehi. Methanolic extract of these plants was analyzed. The DPPH radical scavenging assay was used to measure the antioxidant activity, the Folin-Ciocalteu method to measure total phenolic content, and the aluminum chloride colorimetric method to measure total flavonoid content. Results revealed that plant extract contained phytochemicals such as flavonoids, alkaloids, polyphenols, terpenoids, saponins, quinonnes, etc. The Dioscorea bulbifera showed the highest % of radical scavenging activity up to 82.31±2.43µg/ml with an IC50 value of 51.102±6.424µg/ml followed by Nyctanthes arbortristis and the lowest in Urtica dioica with IC50 value 70.716±1.55 µg/ml, 179.103±3.580 respectively. Dioscorea bulbifera revealed the highest TPC and TFC of 136.667±5.08 mgGAE/g and 33.41±1.720 mgQE/g followed by Nyctanthes arbortristis and lowest in Urtica dioica. These parameters were analyzed from the period of 15 September 2021 to 20 October, 2021.